Inventory Container Information System at PT. Sarana Bandar Nasional - Trias Hendra Rasyid; Teddy Siswanto (Intelmatics, 2021)
Inventory information system is a collection of procedures that are useful for generating inventory information in the company. The system is required by PT. SBN as a service provider of loading and unloading of container goods. PT. SBN must ensure that the container stock available at the port in each branch continues to meet customer needs. The methodology used in developing this system is the waterfall model. At the requirement stage, researchers conduct interviews to user PT. SBN regarding their needs. Then at the design stage researchers create flowchart, DFD, ERD, and application display design. Researchers create a web-based container inventory information system that can provide container availability information in all branches. Availability information can be obtained from transaction data inputted to the system. Transaction data produces a graph to determine the quantity of output information and the container input from the port. This can help the management to make decisions regarding maximum stock levels and minimum containers at each port. Applications in the form of this final prototype have been demonstrated to the PT. SBN and get a good rating because it can run as needed.